Ordinary people, extraordinary times : living the British empire in Jamaica, 1756 - Haggerty, Sheryllynne (McGill-Queen's University Press, 2023)
"In October of 1756, Sarah Folkes wrote home to her children in London from Jamaica. Posted on the ship Europa, bound for London, her letter was one of around 350 letters that were never delivered due to an act of war; they remain together today in The National Archives in London. In Ordinary People, Extraordinary Times Sheryllynne Haggerty closely reads and analyses this collection of correspondence, exploring the everyday lives of poor and middling whites, free people of colour, and the enslaved in mid-eighteenth-century Jamaica--Britain's wealthiest colony of the time--at the start of the Seven Years' War. This unique caché of letters brings to life both thoughts and behaviours that even today appear quite modern: concerns over money, surviving in a war-torn world, family squabbles, poor physical and mental health, and a desire to purchase fashionable consumer goods. The letters also offer a glimpse into the impact of British colonialism on the island; Jamaica was a violent, cruel, and deadly materialistic place dominated by slavery from which all free people benefited, and it is clear that the start of the Seven Years' War heightened the precariousness of enslaved peoples' lives. Jamaica may have been Britain's Caribbean jewel, but its society was heterogeneous and fractured along racial and socioeconomic lines. A rare study of microhistory, Ordinary People, Extraordinary Times paints a picture of daily life in Jamaica against the vast backdrop of transatlantic slavery, war, and the eighteenth-century British Empire."--